Effects of Dietary Beta-Adrenergic Agonist, Terbutaline, on Carcass Characteristics and Blood Attributes in Japanese Quails (Coturnix coturnix japonica) - Boostan MJ (Poultry Science Journal, 2015)
The effect of dietary Terbutaline, a beta adrenergic agonist, on carcass characteristics and blood attributes in 288 Japanese quails was studied from 21 through 49 days of age. Dietary treatments included four levels of Terbutaline [0 (T0), 1 (T1), 3 (T3), and 5 (T5) mg/Kg of the diet]. Quails were bled at the end of the trial for biochemical assays and the carcass characteristics were then measured. The relative weights of breast and drumstick muscles were increased in birds treated with 3 and 5 mg/Kg diet of Terbutaline (P). Regardless of Terbutaline dietary levels included, the weight of subcutaneous and abdominal fat pad was significantly decreased in treated birds (P). The relative weight of heart was increased in T3 treatment group and that of liver was increased in all birds receiving Terbutaline as compared with the control group (P). Irrespective of the dosing level, the percentage of protein in breast muscle was higher in Terbutaline-treated birds (P). However, the fat percentage in drumstick muscle was reduced in birds treated with 3 and 5 mg/Kg diet of Terbutaline, but its protein percentage was increased in T1, T3, and T5 (P). A significant increase in plasma levels of free fatty acids was found in all birds that received Terbutaline (P) as compared with the control. Overally, the data suggested that dietary Terbutaline had a profound positive effect on carcass composition, but a minimal one on the plasma metabolites (glucose, cholesterol, and triglyceride) of Japanese quails.